1992
DOI: 10.1620/tjem.167.89
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carnitine on the Metabolism of Valproic Acid in Epileptic Patients.

Abstract: The half-life of valproic acid (VPA) was studied in 8 epileptic and severely mental retarded patients before and after one month of carnitine supplementation. Serum carnitine concentration was significantly decreased and VPA half-life was prolonged especially in adult patients before carnitine supplementation. After the treatment with carnitine, serum carnitine concentration was increased, and prolonged half-lives of VPA were corrected near to the normal range (from 12.2 + 4.2 hr to 9.7± 2.2 hr ; p <0.05). Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Curiously, evidence to support effectiveness of L-carnitine in improving VPA poisoning is still poor. Reduction in t 1/2 was attributed to L-carnitine in eight non-overdosed long-term VPA-treated patients (9.5 h versus 12 h, P < 0.05) [ 26 ]; however, t 1/2 in this study were shorter compared to ours. A Romanian randomized controlled trial including 62 VPA-poisoned patients admitted to the ICU (28 treated versus 34 non-treated patients with L-carnitine 1,800 mg/day for 3 days) reported that L-carnitine reduced plasma VPA levels and facilitated the decrease in plasma ammonia concentrations [ 27 ].…”
Section: Discussionmentioning
confidence: 51%
“…Curiously, evidence to support effectiveness of L-carnitine in improving VPA poisoning is still poor. Reduction in t 1/2 was attributed to L-carnitine in eight non-overdosed long-term VPA-treated patients (9.5 h versus 12 h, P < 0.05) [ 26 ]; however, t 1/2 in this study were shorter compared to ours. A Romanian randomized controlled trial including 62 VPA-poisoned patients admitted to the ICU (28 treated versus 34 non-treated patients with L-carnitine 1,800 mg/day for 3 days) reported that L-carnitine reduced plasma VPA levels and facilitated the decrease in plasma ammonia concentrations [ 27 ].…”
Section: Discussionmentioning
confidence: 51%
“…Supplementation with L-carnitine leads to normalization of the half-life of VPA. Furthermore, L-carnitine supplementation doesn't seem to shorten the half-life of VPA, which could lead to sub therapeutic levels and subsequent seizures [22]. Animal models also indicate that L-carnitine supplementation has no impact on seizure control in the presence of other AED [23], while leading to increased VPA concentrations within the brain [24].…”
Section: Discussionmentioning
confidence: 99%
“…Kay et al(1986) and Hjelm et al (1986) have reported cases in which occult metabolic disorders were revealed during the administration of VPA. In other studies, L-carnitine supplementation was tried for normalization of carnitine deficiency in VPA-treated patients (Ohtani et al 1982;Sakemi et al 1992). …”
Section: Discussionmentioning
confidence: 99%